The Influence of Online Customer Reviews and Celebrity Endorsement on Purchase Intention of Skin Mandatory Products - Tikki Capriati Marieski; Maria Apsari Sugiat (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The Indonesian cosmetics industry faces intense competition, with local brands like Skin Mandatory struggling to maintain consumer purchase intention in e-commerce settings. This study aims to examine how influencer credibility, influencer attractiveness, and online customer reviews shape consumer attitudes, and their subsequent impact on brand loyalty, brand awareness, electronic word-of-mouth (eWOM), and purchase intention. A quantitative approach was employed, collecting data from 400 respondents who purchased Skin Mandatory products via e-commerce platforms using an online questionnaire with a 5-point Likert scale. Data were analyzed using Partial Least Squares Structural Equation Modelling. The findings confirm that influencer credibility, attractiveness, and online reviews have a significant impact on consumer attitudes, which in turn drive brand loyalty, brand awareness, and eWOM, ultimately influencing purchase intention. However, influencer attractiveness and eWOM showed weaker effects, likely due to a mismatch with the brand’s natural skincare image and low consumer engagement in sharing online recommendations. The study concludes that Skin Mandatory should align influencer selection with its brand identity and enhance eWOM through user-generated content campaigns to boost purchase intention. These findings offer practical strategies for local cosmetic brands to strengthen consumer engagement in competitive e-commerce markets.